Quantifying Medication Exposure in Very Low Birth Weight Neonates - Davis, Natalie L.; Akinmboni, Temitope O.; Mooney, Sandra M. (American Journal of Perinatology, 2019)
Objective Very low birth weight (VLBW) infants are exposed to medications with insufficient evidence describing pharmacokinetics and safety. Objective was to quantify and identify risk factors associated with the highest quartile of medication exposure.Study Design Retrospective record review of VLBW infants admitted to a level-IV neonatal intensive care unit (NICU). We obtained baseline clinical and demographic characteristics, as well as data on all medications received during admission. Characteristics of patients within the upper quartile of medication use were compared with remaining patients.Results Identified 106 infants, mean birth weight (BW) = 961 g, gestational age = 27.3 weeks. Infants received a median = 20 medications (range, 4–72). Those in the top quartile of medication use received ≥30 medications while in the NICU and had higher odds of being male sex, lower BW, longer length of hospital stay (LOHS), and bronchopulmonary dysplasia. Sepsis did not affect medication exposure. Antibiotics, opiates, and reflux medications were among the top prescribed.Conclusion Infants are exposed to a large number of medications during NICU hospitalization, including potentially unnecessary antibiotics and reflux medications. Male sex, the presence of certain comorbidities such as necrotizing enterocolitis, and LOHS, are associated with higher exposure. Increased awareness of this issue may assist in decreasing medication exposure in VLBW populations.
Keywords: very low birth weight; medication exposure; medications; neonates; preterm